Distant yet existent: actor–network theory and the communicative constitution of functionally estranged family relationships. Issue 3 (3rd July 2021) - Allen, Jordan; Allen, Nicole T.
ABSTRACT: Interpersonal and family communication scholarship retains a dualistic approach to relationships and communication. This prevailing logic constrains the ability of critical interpersonal and family communication (CIFC) scholarship to identify communication practices that stabilize unjust operations of power. We argue that CIFC scholarship should make a nonhuman theoretical turn. Specifically, we propose that Bruno Latour's actor–network theory (ANT) provides a way forward for CIFC scholars to identify and critique unjust operations of power that are rendered more and less durable by human and nonhuman communication. To appreciate how ANT could benefit CIFC scholarship, we first identify the ontological and epistemological shifts ANT requires of CIFC scholars. Second, we explore the core uncertainties/controversies of ANT. Third, we embody ANT as a framework to interrogate and critique the communicative constitution of functionally estranged family relationships. Finally, we discuss the value of inviting new materialist approaches to CIFC scholarship.